Photovoltaic characterization of n-CdTe/p-CdMnTe/GaAs diluted magnetic diode - Yahia, I. S.; Yakuphanoğlu, Fahrettin; Chusnutdinow, S.; Wojtowicz, T.; Karczewski, G. (Elsevier, 2013)
A CdTe/CdMnTe heterojunction magnetic diode for photovoltaic applications was fabricated by using molecular beam epitaxy (MBE). The ideality factor and the potential barrier height of the diode were determined to be 1.25 and 0.836 eV, respectively. Photovoltaic parameters of the studied device were determined at various illumination intensities. The highest open circuit voltage of the CdTe/CdMnTe heterostructure was equal to 0.56 V at the illumination intensity of 130 mW/cm(2). The reverse current of the n-CdTe/p-CdMnTe/GaAs diode increases with the increasing illumination intensities. The obtained results suggest that n-CdTe/p-CdMnTe/GaAs diode can be used as a photodiode in photovoltaic and photodetector applications. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: CdTe/CdMnTe; Photovoltaic effect; Current-voltage characterization under dark and illuminations; Photovoltaic parameters